THE PSYCHOLOGICAL ANXIETY AND ITS IMPACT ON THE SERVE RECEPTION PERFORMANCE OF JUNIOR VOLLEYBALL PLAYERS - Assistant. Prof. Dr. Khaled Shaker Mahmoud (Galaxy International Interdisciplinary Research Journal, 2023)
The psychological preparation is an integral part of the teaching process, especially in sports, where the coach’s understanding of the psychological aspect is crucial. The athlete’s personality and behavior play a significant role in personal training, and behavior contributes to cognitive development, providing opportunities for skill improvement, enhancing competition, and attracting spectators. The research focuses on the psychological phenomenon of anxiety as a crucial psychological factor, emphasizing that it should not be solely viewed as a negative factor.